Analisis Komparatif Angka Kemiskinan sebagai Dampak Kebijakan Program Pemberdayaan Ekonomi Keluarga di Kecamatan Leuwigoong Kabupaten Garut - Perceka, Andhika Lungguh (Jurnal Ilmiah Administrasi Publik, 2018)
Comparison of the economy in 2010 and 2016 before and after the policy bycreating an empowerment program to improve the economy of the community. The research method used is an explanatory approach with survey techniques. The population in this study is the poverty rate in the Leuwigoong sub-district which amounts to 8 villages with a total of 4519 families. Prehistoric economic data was obtained from Lewigoong District. From the comparison of the community economy, there is a difference between the economic results of the community before and after the policy because the value of (2-tailed) produces a number of 0.000 <of 0.05 and the results are significant.